从全球和区域角度看公共性和北极治理 - Kristin Bartenstein (《中国海洋法学评论》编辑部, 2015)
Kristin Bartenstein，加拿大魁北克省拉瓦尔大学法学院副教授。 【中文摘要】目前有关北极治理模式的讨论具有一个突出特点，即均会提及公共性。北极国家和非北极国家都提及这一概念，要么是为了支持构建更具排他性的北极合作模式，要么是为了支持构建更具包容性的国际合作模式。本文旨在概述公共性的各种提法，考察其特定内涵，并评估其对北极国家和非北极国家的法律意义，或说明其对这些国家不具有法律意义。通过分析，本文得出了一些初步结论，涉及驱使相关国家提及公共性概念的潜在动机，以及具有隐蔽性但仍在起作用的政治法律偏好。此外，本文起到了抛砖引玉的作用，激励人们反思一个更大的问题，即在构建新的北极治理模式时应予以考虑的法律因素。 【Abstract】In the ongoing discussion regarding the governance model for the Arctic, references to commonality are a salient feature. Made both by Arctic and non-Arctic States, these references are meant to support demands for either a more exclusive, i.e. Arctic, or a more inclusive, i.e. international model of cooperation. The purpose of this paper is to outline the various forms of these references to commonality, investigate their intended meaning and assess their legal implications (or lack thereof) for both Arctic and non-Arctic States. This analysis allows for the drawing of some tentative conclusions regarding the underlying motivations that drive these references as well as the hidden politico-legal preferences at play. It also provides the opportunity to reflect on the broader issue of the legal parameters that need to be respected in devising a new governance model for the Arctic. 加拿大社会科学和人文研宄委员会，以及拉瓦尔大学法学院的资助。